Association of Direct Oral Anticoagulants vs. Vitamin K Antagonists With Fractures in Atrial Fibrillation Patients: A Systematic Review and Meta-Analysis - Wu, Xiaojuan; Hu, Linyan; Liu, Jinjin; Gu, Qiuping (Frontiers in Cardiovascular Medicine, 2021)
Background: Current evidence regarding the application of direct oral anticoagulants (DOACs) vs. vitamin K antagonists (VKAs) on the fracture risk is inconsistent. Therefore, we conducted a meta-analysis to evaluate the fracture risk of DOACs vs. VKAs in patients with atrial fibrillation (AF). Methods: The PubMed and Embase databases were systematically searched until June 2021 for all the studies that reported oral anticoagulants in AF patients. The random-effect model with an inverse variance method was selected to pool the risk ratios (RRs) and 95% confidence intervals (CIs). Results: A total of 10 studies were included in this meta-analysis. Among AF patients receiving anticoagulants, DOAC users showed a reduced risk of any fracture compared to those with VKAs (RR = 0.80; 95% CI: 0.70–0.91) regardless of gender [males (RR = 0.79; 95% CI: 0.67–0.92) and females (RR = 0.71; 95% CI: 0.57–0.89)]. Apixaban (RR = 0.75; 95% CI: 0.60–0.92) and rivaroxaban (RR = 0.73; 95% CI: 0.61–0.88), but not dabigatran and edoxaban, were associated with a decreased risk of any fracture compared with VKAs. DOAC users had decreased risks of osteoporotic fractures (RR = 0.63; 95% CI: 0.47–0.84) and hip/pelvic fractures (RR = 0.88; 95% CI: 0.79–0.97) compared to those treated with VKAs. Conclusions: Our meta-analysis suggested that the use of DOACs was associated with a reduced risk of any fracture compared with VKAs. Further studies should confirm our findings.